Effect of an education program on knowledge, self-care behavior and handwashing competence on prevention of febrile neutropenia among breast cancer patients receiving Doxorubicin and Cyclophosphamide in Chemotherapy Day Centre - Wai Chi Mak; Shirley Siu Yin Ching (Asia-Pacific Journal of Oncology Nursing, 2015)
Objective: To evaluate the efficacy of an education program on the prevention of febrile neutropenia (FN) among breast cancer patients receiving AC regimen. Methods: Randomized controlled trial with the repeated-measures design was conducted in a Chemotherapy Day Centre of an acute hospital in Hong Kong. Twenty-five subjects in the intervention group received an individual education session followed by three follow-up sessions and routine care. Twenty-four subjects in the control group received routine care. Primary outcomes included the incidence of admission due to FN, the self-care behavior adherence, the knowledge level on prevention of FN and the self-efficacy in self-management, handwashing competence were assessed by self-designed questionnaires, Chinese version of patient activation measure, and handwashing competence checklist. Results: No statistically significant difference between the intervention group and the control group on the incidence of admission due to FN, the self-efficacy in self-management, and the knowledge on prevention of FN. The self-care behavior adherence was significant at cycle 4 of AC regimen in favor of the intervention group (P = 0.036). Handwashing competence improved more significantly among subjects in the intervention group than the control group (P = 0.009). Conclusions: The education program on the prevention of FN had significantly favorable effects on self-care behavior adherence and handwashing competence across time. However, the intervention did not lead to statistically significant improvement on the incidence of admission due to FN, the self-efficacy in self-management and the knowledge level on prevention of FN.